Exploring the potential benefits of digital health technology for the management of COPD: a qualitative study of patient perceptions. Issue 2 (10th May 2019) - Slevin, Patrick; Kessie, Threase; Cullen, John; Butler, Marcus W.; Donnelly, Seamas C.; Caulfield, Brian
Engaging chronic obstructive pulmonary disease (COPD) patients to actively participate in self-management has proven difficult. Digital health technology (DHT) promises to facilitate a patient-centred care model for the management of COPD by empowering patients to self-manage effectively. However, digital health studies in COPD have yet to demonstrate significant patient outcomes, suggesting that this research has still to adequately address the needs of patients in the intervention development process. The current study explored COPD patients' perceptions of the potential benefits of DHT in the self-management and treatment of their disease. A sample of convenience was chosen and participants (n=30) were recruited from two Dublin university hospitals and each underwent a qualitative semi-structured interview. Thematic analysis of the data was completed using NVivo 12 software. Six themes were identified: symptom management, anxiety management, interaction with physician, care management, personalising care and preventative intervention. In our findings, patients reported a willingness to take a more active role in self-management using DHT. They perceived DHT potentially enhancing their self-management by improving self-efficacy and engagement and by supporting healthcare professionals to practise preventative care provision. The findings can be used to inform patient-centred COPD digital interventions for researchers and clinicians who wish to develop study aims that align with the needs and preferences of patients. COPD patients perceive potential benefits accruing from using digital health technology in self-management, including improved self-efficacy and perceived support for healthcare professionals to deliver preventative and personalised care http://bit.ly/2DhPMW7